2016
DOI: 10.1016/j.celrep.2016.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Centrosome-Dependent Bypass of the DNA Damage Checkpoint by the Polo Kinase Cdc5

Abstract: Cell-cycle checkpoints are essential feedback mechanisms that promote genome integrity. However, in the face of unrepairable DNA lesions, bypass mechanisms can suppress checkpoint activity and allow cells to resume proliferation. The molecular mechanisms underlying this biological response are currently not understood. Taking advantage of unique separation-of-function mutants, we show that the Polo-like kinase (PLK) Cdc5 uses a phosphopriming-based interaction mechanism to suppress G2/M checkpoint arrest by ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 55 publications
3
34
0
Order By: Relevance
“…[44][45][46][47] Therefore, we can speculate that unprocessed HJs accumulate in the sgs1D cdc5-T238A cells, leading to aberrant chromosome segregation and loss, increase GCRs and hyper-sensitivity to MMS. Most important, our results in Figure 6 on genome rearrangement and chromosome stability, taken together with the recently involvement of Cdc5 in maintaining genome ploidy, 42 further support Cdc5 as key factor to preserve genome integrity.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…[44][45][46][47] Therefore, we can speculate that unprocessed HJs accumulate in the sgs1D cdc5-T238A cells, leading to aberrant chromosome segregation and loss, increase GCRs and hyper-sensitivity to MMS. Most important, our results in Figure 6 on genome rearrangement and chromosome stability, taken together with the recently involvement of Cdc5 in maintaining genome ploidy, 42 further support Cdc5 as key factor to preserve genome integrity.…”
Section: Discussionsupporting
confidence: 77%
“…[17][18][19] Moreover, a clear link between the localization of Cdc5 at centrosomes and checkpoint adaptation to persistent DNA damage and spindle depolarization has been recently established. 42,58 Of interest, we found that the Cdc5-T238A protein variant relocalizes to SPBs with several hours of delay, according to the prolonged cell cycle block after one irreparable DSB (Fig. 4).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Cells carrying the cdc5-ad allele and challenged by an unrepairable DNA damage stay arrested in G2/M and maintain Rad53 in an activated state (Pellicioli et al 2001). Other recently identified adaptation mutants of CDC5 (cdc5-16 and cdc5-T238A) have also contributed to the dissection of Cdc5's role in adaptation (Ratsima et al 2011;Ratsima et al 2016;Rawal et al 2016). However, despite its central role in adaptation, the exact mechanisms by which Cdc5 exerts its function and which Cdc5 targets are affected in response to DNA damage are still unclear (Hu et al 2001;Zhang et al 2009;Donnianni et al 2010;Dotiwala et al 2010;Schleker et al 2010;Vidanes et al 2010;Valerio-Santiago et al 2013;Ratsima et al 2016;Rawal et al 2016;Botchkarev et al 2017).…”
Section: Dna Damage Checkpoint and Adaptationmentioning
confidence: 99%
“…We have previously shown that mutations affecting the phosphopeptide-binding activity of the polo-box domain of Cdc5 are tolerated in yeast as they generate viable alleles that are not associated with strong proliferation defects 35 . However, these alleles show a striking misregulation of cell cycle checkpoints and are defective in their maintenance of genome stability 35,36 . In light of these observations, we wanted to assess the physiological impact of mutations affecting the hydrophobic pocket of the polo-box.…”
mentioning
confidence: 99%